2022
DOI: 10.3389/fenvs.2022.960795
|View full text |Cite
|
Sign up to set email alerts
|

Green energy investment, renewable energy consumption, and carbon neutrality in China

Abstract: This study investigates the dynamic impact of green energy investment and energy consumption on carbon emissions in China from 1995 to 2020. It employed the Bootstrap Autoregressive Distributed Lag method to examine the short and long-run relationship. The long-run findings indicate that green energy investment and renewable energy consumption decrease carbon emissions, whereas non-renewable energy consumption and economic growth increase carbon emissions in shorter and longer periods. The long-term reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…The data was extracted from IRENA. Following recent studies [ 77 , 78 ], this study includes this variable to denote the impact of RE on CDE.…”
Section: Methodsmentioning
confidence: 99%
“…The data was extracted from IRENA. Following recent studies [ 77 , 78 ], this study includes this variable to denote the impact of RE on CDE.…”
Section: Methodsmentioning
confidence: 99%
“…However, it can be predicted that, although China's economic growth rate would show a steady downward trend (2020-2035), the development model of being highly dependent on fossil energy would also not change immediately, inevitably producing a large amount of carbon dioxide. Energy was a major part of emissions, accounting for 80%, but clean energy accounted for only 15% of it [62]. The World Energy Outlook 2019 mentions that the proportion of carbon-neutral clean energy needs to reach more than 65% [63].…”
Section: Current Status Of Carbon Emissionsmentioning
confidence: 99%
“…As the world's largest carbon emitter, China accounts for 28.8% of the world's total energy carbon emissions, which plays a crucial role in global carbon peaking and carbon neutrality [1]. The China Electricity Council's "Power Industry Operation Brief from January to August 2022" showed that by the end of August, the country's installed power generation capacity was 2.47 billion KW, an increase of 8.0% annually, of which coal-fired power generation was 1.11 billion KW, an annual increase of 1.4%, accounting for 45%, and the new installed capacity of coal-fired was 11.2 million KW.…”
Section: Introductionmentioning
confidence: 99%